2020
DOI: 10.5194/bg-2020-361
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Key drivers of pyrogenic carbon redistribution during a simulated rainfall event

Abstract: Abstract. Pyrogenic carbon (PyC) is produced by the incomplete combustion of vegetation during wildfires and is a major and persistent pool of the global carbon (C) cycle. However, its redistribution in the landscape after fires remains largely unknown. Therefore, we conducted rainfall simulation experiments on 0.25-m2 plots with two distinct Swiss forest soils (Cambisol (clay loam) and Luvisol (sandy silt)). We applied PyC produced from wood (Picea abies) labelled under FACE conditions and C4-grass (Miscanthu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…Data availability. The data related to this article are available at https://doi.org/10.5281/zenodo.4422514 (Bellè and Abiven, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Data availability. The data related to this article are available at https://doi.org/10.5281/zenodo.4422514 (Bellè and Abiven, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Actual amounts would depend on site factors such as fire behavior, amount and type of fuel affected, slope steepness, and size of the hydrological event. 6,8 The filter bags had a mesh size < 50 µm to allow the release of small PyC particles and DOC. In the control flumes, filter bags without PyC were added to account for potential riverine DOM interactions with the filter bag.…”
Section: Site Description and Field Experimental Designmentioning
confidence: 99%
“…3 In fire-affected landscapes fresh as well as aged PyC, in both dissolved and particulate forms, is mobilized to fluvial ecosystems via water erosion. [4][5][6] Indeed, significant charcoal presence in river bed deposits in fire affected ecosystems have been the subject of investigation decades ago 7 and hydrological events (e.g. stormwater runoff) can transport large quantities of PyC into river ecosystems in short periods of time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…surface runoff). [3][4][5] Coppola and colleagues 6 found that globally 15.8 ± 0.9% of riverine particulate organic carbon is of pyrogenic origin. Jones and colleagues 7 estimated that PyC accounts for 12 ± 5% of the riverine dissolved organic carbon (DOC, i.e., filtered < 0.45 µm).…”
Section: Introductionmentioning
confidence: 99%